Factors Inhibiting the Implementation of the Package B Program at SPNF SKB Bolangitang, Bolaang Mongondow Utara Regency - Rina Kohongia; Lisda Van Gobel; Kadek Satria Arsana (Formosa Journal of Applied Sciences, 2022)
This study aims to determine the inhibiting factors for the implementation of B Package  in SPNF SKB Bolangitang, North Bolaang Mongondow Regency. In this study, the focus of the problem is socialization, infrastructure, human resources, and budget. The results of this study in terms of several problems that hinder as follows: the socialization that has been carried out has been running but is not optimal due to lack of budget and resources. However, socialization is still carried out with other alternatives, the existing infrastructure facilities in UPTD SPNF SKB Bolangitang indeed still have many shortcomings. it is necessary to make improvements in order to provide the best for the continuity of education, human resources (tutors) in UPTD SPNF SKB Bolangitang are still lacking in need the addition of existing tutors where one tutor teaches more than one lesson so that B package learning is not optimal, the existing budget at UPTD SPNF SKB Bolangitang has a minimal budget which has not been able to meet the learning needs of package B so that the lack of budget cannot increase the number of tutors facility. It is recommended that there is a need for additional human resources, infrastructure, budget and more optimized socialization.